On the Effectiveness of Debt Brakes: The Swiss Experience - Lars P. Feld; Gebhard Kirchgassner (Center for Research in Economics, Management and the Arts (CREMA), 2006)
The Swiss fiscal system is characterised by an extensive fiscal federalism with high fiscal autonomy at all governmental levels, by direct popular rights which include fiscal referenda at the cantonal and local levels, and by particular constitutional and/or statutory fiscal restraints in order to prevent excessive public debt. In this paper, the effects of these constitutional clauses on public deficit and debt are investigated. Using a panel of the 26 Swiss cantons from 1980 to 1998, we provide evidence that fiscal constraints significantly reduce budget deficits, while direct democracy leads to significantly lower public debt.
Keywords: H74; H77; D78; 330; Direct Democracy; Referenda; Initiatives; Public Debt; Budget Deficits